Increased self-focus and diminished informativity: referential and structural properties of narrative speech production in borderline personality disorder - Felletár, Fanni; Vincze, Veronika; Gosztolya, Gábor; Hoffmann, Ildikó; Babarczy, Anna; Unoka, Zsolt Szabolcs (Borderline personality disorder and emotion dysregulation, 2025)
Background Narrative speech production (NSP), i.e., the conceptualization, linguistic formulation, and articulation of a story, is a multifaceted process underpinned by cognitive functions and mentalization ability, often impaired in individuals with borderline personality disorder (BPD). This study examines differences in linguistic formulation between individuals with BPD and healthy controls (HCs), and explores how task type influences linguistic formulation, as well as how linguistic formulation relates to temporal parameters of speech uniquely in BPD. Methods Speech of 33 BPD and 31 HC individuals was recorded in three task types: telling their previous day, retelling a story, and picture sequences. Features of linguistic formulation were extracted with natural language processing methods, while temporal parameters were extracted using automatic speech recognition. Hypothesis-driven generalized linear mixed-effects models (GLMMs) were applied to test predefined group differences in four linguistic features (content words, first- and third-person singular verbs, and syntactic complexity). Additional exploratory GLMMs examined other linguistic features and task effects. Within-group Spearman correlations assessed associations between linguistic and temporal measures, controlling for task. Results Hypothesis testing showed that the NSP in BPD is characterized by fewer content words, more first-person singular verbs, and lower syntactic complexity than that of HCs. Exploratory analyses revealed that individuals with BPD used pronouns more frequently than HCs, particularly demonstrative pronouns (e.g., this ) and first-person singular pronouns (e.g., I ). In BPD, higher first-person singular reference (pronouns and verbs) correlated with fewer silent pauses, while greater syntactic complexity correlated with more filled pauses. Task modulated verbosity and the use of other pronoun types. Conclusions Findings suggest that NSP in BPD is characterized by dominant self-referential thought content, reflected in elevated first-person singular reference, and by qualitatively impoverished language use, marked by reduced content word production, increased pronoun use, and lower syntactic complexity. Heightened self-focus may hinder the efficient allocation of cognitive resources required for cohesive, listener-oriented NSP.